Rohm and Haas stockholder exhibit on plastics - Rohm and Haas Company (1964)
General view of an exhibit panel on plastics, specifically Plexiglas, exhibited at the 1964 Rohm and Haas Company stockholders' meeting. The left-hand side of the panel features a Gulf service station sign molded of Plexiglas, with accompanying text detailing the use of Plexiglas at more than 35,000 individual service stations. The right-hand side of the panel features a variety of automobile tail lights molded of Plexiglas, with accompanying text highlighting the material's clarity and durability. The Rohm and Haas Company was founded in 1907 in Esslingen, Germany through the partnership of German chemist Otto Röhm and German businessman Otto Haas. In 1933, Röhm's experiments with the polymerization of methyl methacrylate led to the creation of a clear, solid plastic sheet, which he trademarked Plexiglas. During World War II, the demand for Plexiglas, which both Allied and Axis forces used for submarine periscopes and aircraft windshields, canopies, and gun turrets, helped transform Rohm and Haas into a major chemical firm.
Keywords: Rohm and Haas Company; Chemical industry; Corporations; Plastics; Plastics industry and trade; Automobiles--Parts; Automobile supplies industry; Gulf Oil Corporation; Signs and signboards